Kebenaran Sebagai Misteri: Tinjauan Epistemologis Terhadap Konsep Spiritualisme Kritis Ayu Utami - Hasan Labiqul Aqil (LPPM STKIP PGRI Bandar Lampung, 2026)
This study departs from the problem of the dichotomy between positivistic rationalism and religious dogmatism, both of which reduce truth to absolute claims. It aims to formulate the position of “mystery” as an epistemic category within the concept of Critical Spiritualism developed by Ayu Utami. The research employs a qualitative approach based on library research with a descriptive-analytical method, combined with philosophical hermeneutic analysis of Utami’s major works, particularly Simple Miracles (2014), Anatomi Rasa (2019), and the essay Critical Spiritualism (2015). The findings reveal that “mystery” is not positioned as ignorance, but as an epistemic horizon that preserves the openness of knowledge and resists claims of totality. This concept gives rise to epistemic humility, which functions as a critique of both scientific and religious absolutism. The discussion shows that Critical Spiritualism operates as an integrative epistemological model that connects reason, experience, and the spiritual dimension in a dialogical manner without falling into relativism. In conclusion, truth within this framework is processual, partial, and open-ended, making it more relevant for contemporary plural societies. The contribution of this study lies in formulating mystery as a valid mode of knowledge while also serving as an ethical foundation to prevent ideological domination in claims of truth.